IMPLEMENTASI DIGITALISASI LAPORAN KEUANGAN PADA USAHA MIKRO KECIL DAN MENENGAH - Arie Rachma Putri; Humairoh Al Hakim; Amanda Oktavia; Agil Bayu Winoto (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the implementation of financial report digitalization among Micro, Small, and Medium Enterprises (MSMEs) in Delanggu, Klaten. Using a descriptive quantitative approach, data were collected through questionnaires, observations, and interviews from 20 MSME actors selected by purposive sampling. Four key indicators were examined, namely understanding, implementation, obstacles, and opportunities related to financial digitalization. The results show that the level of understanding of MSME actors regarding the importance of digital financial reporting is high (average score 3.92), while the implementation level is categorized as moderate (average score 3.31). The main obstacles identified include limited digital skills, perceived cost burdens, and the habit of manual bookkeeping (average score 3.18). Nevertheless, the opportunities for digitalization are significant, particularly in improving financial management efficiency, expanding market access, and supporting access to financing (average score 3.78). These findings indicate that although the awareness of digital financial reporting is strong, support and continuous assistance are still needed to increase the adoption rate. The study contributes empirically by providing real field-based insights into the readiness and challenges of MSMEs in adopting digital financial reporting systems.